OPTIMIZATION OF B-SERIES PROPELLER DESIGN AS KCR 60 PROPULSOR TO ACHIEVE OPTIMAL PERFORMANCE USING MATHEMATICAL MODEL - Akhmat Nuryadin; Abdul Rahman; Cahyanto Cahyanto (Indonesian Naval Technology College - Sekolah Tinggi Teknologi Angkatan Laut - STTAL, 2019)
The process of designing a propeller as a ship propulsor is an important step to produce a propeller that has the ability to achieve the desired target speed of the ship. Propeller optimization is an effort to produce a propeller design with optimal capabilities. This propeller design uses a B-series propeller where this propeller is commonly used as ship propulsor. Optimization steps to find the optimal propeller, namely: determining the objective function, determining the decision variable, and determining the constraint variable. The objective function of this optimization is to determine the Advanced-optimal (J-opt) coefficient value for the propeller. The J-opt coefficient must have a value greater than the J-Design coefficient (J-d) value and the smallest possible value (minimization function). For decision variables include picth diameter ratio (P / D) and Blade area ratio (Ae / Ao) and number of leaves (Z). While the constraint variables are: the pitch diameter ratio value of the B-series propeller (0.5≤P/D≤1.4), the blade area ratio B-series (0.3≤Ae/Ao≤1, 05) as well as the number of blade (2≤Z≤7). From the calculation results of the optimization of the B-series propeller design for the KCR 60, the optimum value is different for each blade. the propeller with the number of blade 2 (Z = 2) obtained the optimum propeller with the value of J-opt =0.77098733, Ae/Ao=0.3, P/D=1.13162337, KT = 0.165632781, 10KQ=0, 27546033 and efficiency=0.73198988. Popeller with number of blades 3 (Z=3) obtained optimum propeller with J-opt value=0.77755594, Ae/Ao=0.3, P/D=1.06370107, KT=0.168069763, 10KQ=0.28984068 and efficiency=0.70590799. Propeller with number of blades 4 (Z=4) obtained optimum propeller with J-opt value=0.78478688, Ae/Ao=0.45954773, P/D=1.03798312, Kt=0.172147709, 10Kq= 0.3091063 and efficiency=0.67797119. Propeller with blades number 5(Z=5) obtained optimum propeller with J-opt value=0.78575616, Ae/Ao=0.65607164, P/D=1.02716571, KT=0.174099168, 10KQ=0.31376705 and efficiency=0.67547177. Propeller with blades number 6 (z=6) obtained optimum propeller with J-opt value=0.78867357, Ae/Ao=0.71124343, P/D=1.0185055, KT=0.176525247, 10KQ=0.32215257 and efficiency =0.66705719. Propeller with number of blades 7 (Z=7) obtained optimum propeller with J-opt value=0.7949898, Ae/Ao=0.69772623, P/D=1.01780081, KT=0.181054792, KQ=0.34011349 , and efficiency =0.64804328.Keywords : KCR, Optimization,Wageningen B-series.